Media Education and the Tamil Community: A View from the North and East - Raguram, S. (My University, 2015)
As communication, in addition to food, clothing and shelter, has increasingly come to be seen as a basic need for the individual and society, the influence of the media and communications has grown in importance as a theme for research. Media education is vital in promoting an understanding of the media, reinforcing the utilization of media as a means of meeting human needs, and encouraging a critical perspective on media usage. The practical issue is to consider what types of media education - formal or informal – should be pursued. Formal media education can be carried out within an institution, within a formal structure and with defined objectives. By contrast, media education for a wider public can be informal and use more flexible educational methods. In Sri Lanka, there are many informal educational approaches towards media at different levels. But formal institutional approaches to media education are comparatively weak. At the initial stages, media education in the universities was introduced almost as a token subject and largely involved media appreciation. This proved a constraint in understanding the significance and potential of media education. A number of universities in Sri Lanka have a good record in considering the fundamentals of media education as part of their curricula. However, in the universities of the North and East, it is only recently that media education has become a major field of study. There are many reasons for this. Colombo was considered as the hub of the mass media, although Jaffna in northern Sri Lanka and Batticaloa in the eastern province have a long record of journalism both in Tamil and in English at the regional level. Compared with universities in Colombo, the Northern and Eastern universities were not pioneers in media education. In the North and the East, the media were rich in literary, cultural and religious content but they were not the subject of structured media education. The long standing war and its consequences played a major role in this. Media education was affected by a variety of factors, including continuous attacks on media outlets in Jaffna from the period of the Indian Peace Keeping Force, aerial bombardment and shelling during the 80s and 90s, and mass displacement and control over the local media by rebels. The economic embargo enforced by successive Sri Lankan governments on movements of goods and services to the North created additional obstacles to the development of the media during the war days. For all these reasons, media education could not (as in other parts of the island) reach the desired level. This was partly because education as a whole was disrupted, partly because for many Tamil inhabitants of these areas media education was not seen as a priority. During the war days, the Tamil media operated under considerable political and economic pressures. They were not generating large profits and journalism was a dangerous and poorly paid profession. In general, Tamil families encouraged their children to go into better paid professions and trades rather than taking the risks involved in entering the media field. The traditional mindset of Tamil families towards seeking government jobs also made them steer clear of encouraging their children to pursue a media education.